Tinjauan Yuridis Penanganan Kejahatan Siber (Cybercrime) Di Sektor Perbankan Indonesia Dan Amerika - Rina Shahriyani Shahrullah; Delfind Kiweikhang (Fakultas Hukum, Universitas Internasional Batam, 2014)
Considering that the effect of Information Technology is worldwide and borderless, the jurisdiction concept is not only applicable in the territory of Indonesia but also in the territory of United States of America both country that is largely affected with the impact of cybercrime. Cybercrime deeply effected the interest of both country, government, population and their economic. There were so many kinds of cyberspace offenses, principally offense that should be applied is a formal offense, considering the criminal act of cyberspace element of loss is often even harder to prove because it is cross-territorial and unawareness of the victim, even if the offender and evidence have already been caught.This research is a sociological law by using the method of comparative law. Sources of data used in the form of primary and secondary data sources. Data mining is done with field research and literature study (library research). After all the data collected, the data is then processed and analyzed, the qualitative analysis is used with the intention to classify aspects of data studied. Furthermore, it is concluded that the research associated with this, then described descriptively.Based on the results of this study showed that there are some similarities and differences in the conception of cybercrime offences in Indonesia and United States of America. However, in terms of legal liability, the provisions of the United state of America to regulate is better than Indonesia, seen in terms and strategy to overcome the offences and to prevent the occurrence of cyberspace offence.